The ecology of reproduction in long-lived male Alpine ibex (Capra ibex): the role of age, dominance and alternative mating tactics - Willisch, Christian S. (My University, 2009)
Since basic information on reproductive behaviour in male Alpine ibex was lacking, I provided in chapter 1, first a detailed description of the mating system and the two alternative mating tactics in this species. I investigated to which extent the adoption of these observed mating tactics in male Alpine ibex can contribute to the exceptional survival described in this species. Some males adopted a tactic termed ‘tending’ to monopolize individual, receptive females by following and defending them persistently against their competitors that tried to sneak copulations via the so called ‘coursing’ tactic. The adoption of the two tactics was strongly age-dependent with older males engaging primarily in the tending tactic while younger males typically used the coursing tactic. With regard to the observed copulations, tending appeared to be the more successful tactic, although some copulations were also the result of coursing. However, males adopting the coursing tactic spent more time in low-cost and less time in high-cost behaviors than males adopting the tending tactic. Time budget comparisons with another ungulate species suggested that while tending is a relatively costly tactic, coursing is a low-cost tactic that might contribute to the exceptional adult survival in male Alpine ibex. Because of the supposed small energetic costs male Alpine ibex appeared to incur during the rut and the fact that they are aggregating in social groups, I tested in chapter 2, whether energy-intensive agonistic interactions among competing males might be reduced during the rut as a result of a pre-established and binding dominance hierarchies among them. In accordance with our hypothesis, male Alpine ibex decreased the time spent in agonistic interactions and the number of horn fights during the rut compared to the pre-rut. As expected, changes between access-holding males occurred always without foregoing horn fights and were entirely based on pre-established, stable dominance relationships. Subordinate males either left the consort pair or they adopted the coursing tactic in order to achieve temporary access to estrus females. They behaved extremely reluctant towards dominants, as they never used overt aggression to challenge them or to create actively transient mating opportunities. Overall, male Alpine ibex appeared to be able to cut down on energy-expenditures associated with agonistic interactions by the adherence to pre-established and stable dominance relationships among them, what in turn was likely to contribute to their superior survival. In chapter 3, we analyzed within a Bayesian framework the effects of age, dominance and mating tactics on the likelihood of paternity in male Alpine ibex. Based on life-history considerations, reproductive success in male Alpine ibex was expected to be comparatively heavily skewed towards older, dominant males making primarily use of a tactic to monopolize access to receptive females, while younger, subordinate males trying to steal copulations from access-defending males via a ‘sneaking’ tactic were predicted to sire only sporadically offspring. In accordance with our hypothesis, reproductive success was heavily skewed towards older, dominant males that typically monopolized access to receptive females by the adoption of the ‘tending’ tactic, while success among young, subordinate males via the sneaking tactic ‘coursing’ was overall low and rare. Compared with other ungulates with higher mortality rates, reproduction among young male Alpine ibex was overall lower and more sporadic. Finally, a relatively high reproductive skew emerged, denoting a big potential for selection in male Alpine ibex. The findings support the theory that survival perspectives of males modulate the investments into reproduction via alternative mating tactics early in life.
Thèse de doctorat : Université de Neuchâtel, 2009 ; Th. 2102